2009
DOI: 10.1002/jcb.22227
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers for prostate cancer

Abstract: The detection of prostate cancer using a blood test has by many standards changed the face of the disease. Despite this tremendous success, there are limitations attributed to the use of prostate specific antigen (PSA) as a means to screen and detect prostate cancer. PSA, as its name implies, is not specific for prostate cancer and as such is often found elevated in other prostatic diseases/symptoms associated with the aging male. Clearly, more specific marker(s) that could identify which individuals actually … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(31 citation statements)
references
References 47 publications
0
30
0
1
Order By: Relevance
“…Monitoring of PSA is generally recommended in men over 50 years old to screen for prostate cancer; however, there is significant controversy with respect to its use as a marker for the appearance of the disease (1)(2)(3)(4)(5)(6). By contrast, substantial data support its use in monitoring progression and metastasis (1,2,5). Recently, a Phase II controlled trial suggested that immunization against PSA prolongs patient survival, suggesting a direct role for PSA in the pathobiology of the disease (7).…”
Section: Prostate-specific Antigen (Psa)mentioning
confidence: 99%
“…Monitoring of PSA is generally recommended in men over 50 years old to screen for prostate cancer; however, there is significant controversy with respect to its use as a marker for the appearance of the disease (1)(2)(3)(4)(5)(6). By contrast, substantial data support its use in monitoring progression and metastasis (1,2,5). Recently, a Phase II controlled trial suggested that immunization against PSA prolongs patient survival, suggesting a direct role for PSA in the pathobiology of the disease (7).…”
Section: Prostate-specific Antigen (Psa)mentioning
confidence: 99%
“…To overcome the PSA limitations, a series of new biomolecules, including cellular and genetic biomarkers, such as PCA3 [4], AMACR [5], specific metalloproteinases [6] and glycan profiles [7], are proposed for PCa screening [8]. Simultaneously, a search for a more sensitive, accurate and reliable biomolecule objectively measureable in accessible fluids, such as serum, is pursued, together with the development of a robust, easy-to-use, clinical test, based on novel biomarkers that could improve not only the diagnosis but also prognosis and management of this cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Yes, the clinical method for screening EPCa is prostate specific antigen (PSA) test. 2 But unfortunately, PSA test has been found to be unreliable in practice. Both the false negative rate (15.2%) and false positive rate (30%) are very high, though it is the most widely used clinical method for EPCa.…”
mentioning
confidence: 99%